Weed dynamics and productivity of dry direct seeded rice in relation to tillage and weed management practices - Marasini, D.; Sah, S. K.; Marahatta, S.; Dhakal, S. (Journal of Agriculture and Forestry University, 2020)
Weed is one of the major constraints for success of dry direct seeded rice (DDSR) technology. The productivity, weed density and weed dry weight of DDSR is influenced by weed management practices. A field experiment was done to evaluate tillage methods and weed management practices on weed dynamics and yield of DDSR using split plot design; each treatment replicated thrice. The treatment consisted of two tillage methods in the main plots, and eight weed management practices in the sub-plots. Gorakhnath-509 was the variety of rice used. Weed flora observed in the experiment comprised of 25 weed species, belonging to 12 families. Among them 12 were broadleaf weed, belonging to 10 families; 8 were grasses, belonging to Poaceae family, and the rest 5 were sedges, belonging to Cyperaceae family. Tillage methods did not influence weed density and weed dry weight in DDSR, but weed management practices reduced weed density and dry weight at all dates of observation compared to weedy check. All the weed management practices significantly improved the grain yield of DDSR in both tillage methods. Treatments with higher grain yield of DDSR were, use of pendimethalin followed by hand weeding (3,742 kg ha-1); pendimethalin followed by bispyribac-Na (3,552 kg ha-1), and pendimethalin followed by tank mixture application of bispyribac-Na and ethoxysulfuron(3,638 kg ha-1), but were statistically similar (p>0.05). Results thus supports the fact that application of popular pre-emergence herbicide- pendimethalin followed by manual weeding, or post-emergence herbicide, such as Bispyribac-Na, or tank mixture of post emergence herbicides bispyribac-Na and Ethoxysulfuron could be the most effective weed management practices in both tillage method of rice cultivation.